2011
DOI: 10.2522/ptj.20100267
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Articles Published from 1980 to 2009 in Physical Therapy, Journal of the American Physical Therapy Association

Abstract: Purpose: The purpose of this study was to understand how to eff ectively perform joint traction by analyzing the distance change of the joint space (separation distance) induced by continuous traction of the knee joint. Method: A total of 42 healthy subjects were divided into three groups based on traction strength (100, 150, and 200 N group). We then analyzed the separation distance using ultrasound images of the joint space, before and during knee joint traction (5, 10, 30, 60, 120, 180 s) at 50° fl exion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 24 publications
2
50
0
6
Order By: Relevance
“…A maximum of 2 intervention codes could be selected and 3 clinical condition entries made. Readers interested in more detail on the intervention codes are encouraged to refer to the previous publication, 4 which contains a more thorough description and expanded definitions. Reliability of the Coding System We conducted 3 separate intertester reliability trials, similar to those described in our previous study.…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum of 2 intervention codes could be selected and 3 clinical condition entries made. Readers interested in more detail on the intervention codes are encouraged to refer to the previous publication, 4 which contains a more thorough description and expanded definitions. Reliability of the Coding System We conducted 3 separate intertester reliability trials, similar to those described in our previous study.…”
Section: Content Analysismentioning
confidence: 99%
“…5,11,10,16 Recently, Mogil et al 14 performed a comprehensive bibliometric analysis of the journal Pain, examining 32 years of published pain research. 14 Similarly, we examined the content of Physical Therapy (PTJ), the official journal of the American Physical Therapy Association (APTA) 4 In that analysis, our aim was to describe publication and citation patterns among multiple article types over 30 years. These analyses allowed for inferences related to physical therapy practice and research from a broad-based perspective; but conclusions related to specialty areas of physical therapy practice (eg, orthopaedics and sports) were limited.…”
mentioning
confidence: 99%
“…For example, qualitative methodologies may be more appropriate for obtaining information on clients' experiences and feelings. 7 The amount of published PT literature has increased significantly over the years: [10][11][12][13][14] Wiles and colleagues 12 found that the number of articles published in Physical Therapy doubled from 1945 to 2010, Fell and colleagues 13 found that the number of articles indexed in Medline more than doubled between 2000 and 2009, and Kumar and colleagues found that there was a sharp increase in PT publications in PubMed from 2000 to 2010. 14 Trends in types of PT literature have also been evaluated.…”
Section: Ré Sumémentioning
confidence: 99%
“…Wiles and colleagues 12 found that systematic reviews, cohort studies, and non-randomized controlled trials in Physical Therapy increased in prevalence from 1945 to 2010; Coronado and colleagues 10 found an increased percentage of research reports, systematic reviews, and qualitative studies, but a decrease in topical reviews and non-systematic reports from 1980 to 2009, with no change in case reports or RCTs. 10 More recently, Kumar and colleagues 14 examined PT literature in PubMed between 1970 and 2010; they found that clinical trials, RCTs, and review articles were most prevalent, with a rapid increase after 1995.…”
Section: Ré Sumémentioning
confidence: 99%
See 1 more Smart Citation